Corneal sustained delivery of hyaluronic acid from nanofiber-containing ring-implanted contact lens. (January 2023) - Akbari, Elham; Imani, Rana; Shokrollahi, Parvin; Heidari keshel, Saeed
Dry eye syndrome, as a persist corneal epithelial defect (PED), is an inconvenient ocular disorder that is generally treated by high-dosage, conventional eye drops. Addressing low efficacy and rather restricted bioavailability of the conventional eye drops, drug-eluting contact lenses (CLs) are widely used as alternatives in ophthalmic drug delivery applications. In the present study, a nanofiber-containing ring implant poly (vinyl alcohol) (PVA) hydrogel is designed as a carrier for hyaluronic acid (HA) delivery. hyaluronic acid is physically encapsulated in a nanofiber-containing ring-shaped hydrogel with a 2 mm width that is implanted in the final CLs hydrogel. The designed CL has 59% porosity, 275% swelling ratio and undergoes no weight loss at physiological conditions in14 days. In-vitro release studies were performed on the CLs with and without nanofibers. The results showed that nanofiber incorporation in the designed CL was highly influential in decreasing burst release and supported sustained release of HA over 14 days. In addition, nanofiber incorporation in the designed system strengthened the lens, and the young modulus of the PVA hydrogel increased from 6 to 10 kPa. Cell viability study also revealed no cell cytotoxicity and cell attachment. Overall, the study demonstrated the effective role of nanofibers in the physical strengthening of the CL. Also, the designed system holds promise as a potential candidate for HA delivery over an extended period for treating dry eye syndrome. Graphical Abstract